Charter of Social Rights of the Council of Europe - Swiatkowski, Andrzej (The Hague, 2007)
"The legal term “social rights” refers to the specific human rights addressed by labour law and social security law. On the European continent, these rights are protected not only by domestic law, but also by the European Social Charter of the Council of Europe of 1961, its three additional protocols (1988, 1991, and 1995), and the Revised European Social Charter of 1996. These instruments comprise a fundamental international treaty which not only specifies the relevant rights but also includes an array of supervisory mechanisms to monitor compliance, a regulatory role undertaken by the European Committee of Social Rights. This important book offers an in-depth analysis of the substantive and procedural issues of protecting social rights in Europe under the Social Charter. Analysing the standards promulgated by the Committee, and drawing on the extensive legal literature on the subject, the author focuses on the administrative aspects of all the social protections afforded by the Charter, including the following: